The impact of policy elements on the financing costs of RE investment: The case of wind power in Germany - Olaf Giebel; Barbara Breitschopf (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2011)
Renewable energy support mechanisms affect the attractiveness of projects by influencing uncertainties in revenues or expenditures and ultimately result in a change in the financing costs. The influence of feed-in tariffs on financing costs was investigated. 26 wind onshore investors were surveyed in a conjoint analysis and the results were used in a cash flow model to quantify the impact. The introduction of premium models under a fixed remuneration tariff scheme seems to increase the financing costs considerably.
Keywords: 330